Marketing research and customer analytics: interfunctional knowledge integration. (29th February 2008) - Lichtenstein, Sharman; Bednall, David H.B.; Adam, Stewart
The Customer Analytics (CA) function is increasingly leveraged for Customer Relationship Management (CRM), however it may lack the value of marketing knowledge available from the Marketing Research (MR) function due to inadequate interfunctional knowledge integration. This paper develops a set of sixteen propositions from a synthesis of the marketing and knowledge management literatures relating key organisational influences on the integration of knowledge between the MR and CA functions. A range of strategic, cultural, structural and technical influences is reflected by the propositions. It is planned to test the propositions in future empirical research.